Anode active material, anode including the same, secondary battery including the same, and method for producing anode active material
A SiO x (0<x<2) negative electrode active material with a carbon layer and Ca-containing inorganic layer addresses the inefficiencies of silicon-based electrodes by reducing water reactivity and enhancing discharge capacity and battery performance.
Patent Information
- Application Number
- JP2024539991
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-13
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-14
AI Technical Summary
Silicon-based negative electrode active materials in lithium secondary batteries suffer from high irreversible capacity and reduced initial efficiency due to volumetric expansion/contraction during charging and discharging, and the presence of metal-doped silicon-based oxides react with moisture, affecting the pH and viscosity of the negative electrode slurry.
A negative electrode active material comprising SiO x (0
Improves the aqueous processability of the slurry, enhancing discharge capacity, initial efficiency, resistance performance, and battery life characteristics by preventing water penetration and side reactions.
Smart Images

Figure 2025501990000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material, a negative electrode including the same, a secondary battery including the same, and a method for producing the negative electrode active material.
[0002] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0091036 filed with the Korean Intellectual Property Office on July 22, 2022, and the benefit of the filing date of Korean Patent Application No. 10-2023-0090935 filed with the Korean Intellectual Property Office on July 13, 2023, the entire contents of which are incorporated herein by reference. [Background technology]
[0003] Recently, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have a relatively high capacity is rapidly increasing. In particular, lithium secondary batteries are in the spotlight as a driving power source for portable devices because of their light weight and high energy density. As a result, research and development efforts to improve the performance of lithium secondary batteries are being actively carried out.
[0004] In general, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, and an organic solvent. In addition, the positive electrode and the negative electrode may have active material layers formed on current collectors, each of which includes a positive electrode active material and a negative electrode active material. In general, the positive electrode uses a lithium-containing metal oxide such as LiCoO2 or LiMn2O4 as a positive electrode active material, and the negative electrode uses a lithium-free carbon-based active material or a silicon-based active material as a negative electrode active material.
[0005] Silicon-based negative active materials have been attracting attention because they have higher capacity and excellent high-speed charging characteristics compared to carbon-based active materials. However, silicon-based active materials have the disadvantage of low initial efficiency due to large volume expansion / contraction during charging / discharging and large irreversible capacity.
[0006] On the one hand, in the case of silicon-based active materials, specifically silicon-based oxides represented by SiOx (0 < x < 2), there is an advantage in that the degree of volume expansion / shrinkage due to charge / discharge is lower compared to other silicon-based active materials such as silicon (Si). However, there is still a disadvantage in that the initial efficiency of silicon-based oxides is reduced due to the presence of irreversible capacity.
[0007] Regarding this, research has been continuously conducted to reduce the irreversible capacity and improve the initial efficiency by doping or inserting metals such as Li, Al, and Mg into silicon-based oxides. However, in the case of a negative electrode slurry containing a metal-doped silicon-based oxide as a negative electrode active material, there is a problem that the metal oxide formed by doping reacts with moisture to increase the pH of the negative electrode slurry and change the viscosity, thereby deteriorating the state of the manufactured negative electrode and reducing the charge / discharge efficiency of the negative electrode.
[0008] Therefore, there is a need to develop a negative electrode active material that can improve the phase stability of a negative electrode slurry containing a silicon-based oxide and improve the charge / discharge efficiency of the negative electrode manufactured therefrom.
[0009] Korean Registered Patent No. 10-0794192 relates to a method for manufacturing a carbon-coated silicon-graphite composite negative electrode material for a lithium secondary battery and a method for manufacturing a secondary battery including the same, but there are limitations in solving the above problems.
Summary of the Invention
Problems to be Solved by the Invention
[0010] The present invention relates to a negative electrode active material, a negative electrode including the same, a secondary battery including the same, and a method for manufacturing the negative electrode active material.
Means for Solving the Problems
[0011] One embodiment of the present invention is SiO xSilicon-based particles containing (0 < x < 2) and a Li compound, and having a carbon layer provided on at least a part of the surface; and an inorganic layer containing Ca provided on at least a part of the silicon-based particles are provided as a negative electrode active material.
[0012] One embodiment of the present invention provides a negative electrode containing the negative electrode active material.
[0013] One embodiment of the present invention provides a secondary battery containing the negative electrode.
[0014] One embodiment of the present invention is SiO x Forming silicon-based particles containing (0 < x < 2) and a Li compound, and having a carbon layer provided on at least a part of the surface; and reacting the silicon-based particles with a Ca precursor; A method for manufacturing the negative electrode active material is provided.
Advantages of the Invention
[0015] The negative electrode active material according to one embodiment of the present invention includes an inorganic layer containing Ca, and thus has the effect of improving the water-based processability of the slurry. Specifically, the inorganic layer containing Ca has low reactivity with water. Thereby, the inorganic layer does not react with water in the aqueous slurry and is well retained, preventing water from penetrating into the negative electrode active material, so that the silicon-based particles can be efficiently passivated. In addition, it has the effect of improving the water-based processability of the slurry by preventing side reactions between the silicon-based particles or lithium by-products and water and suppressing gas generation.
[0016] Therefore, a negative electrode containing the negative electrode active material according to one embodiment of the present invention, and a secondary battery containing the negative electrode have the effect of improving the discharge capacity, initial efficiency, resistance performance and / or life characteristics of the battery.
Brief Description of the Drawings
[0017] [Figure 1] Relates to the XRD analysis result of the negative electrode active material of Example 1. [Diagram 2]1 relates to the results of XRD analysis of the negative electrode active material of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] This specification will be explained in more detail below.
[0019] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0020] In this specification, when a member is said to be located "on" another member, this includes not only the case where the member is in contact with the other member, but also the case where another member is present between the two members.
[0021] The terms and words used in this specification should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0022] As used herein, the singular expression of a term includes the plural expression unless the context clearly indicates otherwise.
[0023] In this specification, the crystallinity of the structure contained in the negative electrode active material can be confirmed by X-ray diffraction analysis, which may be performed using an X-ray diffraction (XRD) analysis device (product name: D4-endavor, manufacturer: Bruker), or other devices used in the industry may be appropriately adopted.
[0024] In this specification, the presence or absence of an element in the negative active material and the content of the element may be confirmed by ICP analysis, and the ICP analysis may be performed using an inductively coupled plasma optical emission spectrometry (ICPAES, Perkin-Elmer 7300).
[0025] In this specification, the average particle size (D 50 ) can be defined as the particle size at the 50% reference of the volume cumulative amount in the particle size distribution curve (graph curve of the particle size distribution diagram) of the particles. The average particle size (D 50 ) can be measured, for example, using the laser diffraction method. The laser diffraction method can generally measure particle sizes in the submicron region to about several millimeters, and results with high reproducibility and high resolution can be obtained.
[0026] Hereinafter, preferred embodiments of the present invention will be described in detail. However, the embodiments of the present invention may be modified into various forms, and the scope of the present invention is not limited to the embodiments described below.
[0027] <Negative electrode active material> One embodiment of the present invention includes silicon-based particles containing SiO x (0 < x < 2) and a Li compound, and having a carbon layer provided on at least a part of the surface; and an inorganic layer containing Ca provided on at least a part of the silicon-based particles; to provide a negative electrode active material.
[0028] The negative electrode active material according to one embodiment of the present invention includes silicon-based particles. The silicon-based particles contain SiO x (0 < x < 2) and a Li compound.
[0029] The SiO x (0 < x < 2) may correspond to a matrix in the silicon-based particles. The SiO x (0 < x < 2) may be in a form containing Si and / or SiO2, and the Si may form a phase. That is, x corresponds to the number ratio of 0 to Si contained in the SiO x (0 < x < 2). When the silicon-based particles contain the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.
[0030] The Li compound can correspond to a matrix within the silicon-based particles. The Li compound can exist in at least one form of lithium atom, lithium silicate, silicide, and lithium oxide within the silicon-based particles. When the silicon-based particles contain the Li compound, it has the effect of improving the initial efficiency.
[0031] The Li compound can be distributed on the surface and / or inside of the silicon-based particles in a form doped into the silicon-based particles. The Li compound is distributed on the surface and / or inside of the silicon-based particles, and can control the volume expansion / contraction of the silicon-based particles to an appropriate level, and can play a role in preventing damage to the active material. In addition, the Li compound can be contained in terms of reducing the ratio of the irreversible phase (e.g., SiO2) of the silicon-based oxide particles and increasing the efficiency of the active material.
[0032] In one embodiment of the present invention, the Li compound may exist in the form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 within the silicon-based particles, and the amorphous lithium silicate may have a complex structure of the form Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.
[0033] In one embodiment of the present invention, Li may be included in an amount of 0.1 to 40 parts by weight or 0.1 to 25 parts by weight based on 100 parts by weight of the total negative active material. Specifically, Li may be included in an amount of 1 to 25 parts by weight, and more specifically, Li may be included in an amount of 2 to 20 parts by weight. As the Li content increases, the initial efficiency increases but the discharge capacity decreases, so that when the Li content is within the above range, appropriate discharge capacity and initial efficiency can be realized.
[0034] The content of the Li element can be confirmed by ICP analysis. Specifically, a certain amount (about 0.01 g) of the negative electrode active material is taken, transferred to a platinum crucible, and completely decomposed on a hot plate by adding nitric acid, hydrofluoric acid, and sulfuric acid. Then, an inductively coupled plasma emission spectrometry (ICPAES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at the characteristic wavelength of the element to be analyzed, and a reference calibration curve is created. Then, the pretreated sample solution and a blank sample are introduced into the device, and the intensity of each is measured to calculate the actual intensity. The concentration of each component is calculated by comparing it with the created calibration curve, and the total sum is converted to a theoretical value, so that the element content of the manufactured negative electrode active material can be analyzed.
[0035] In one embodiment of the present invention, the silicon-based particles may include additional metal atoms. The metal atoms may be present in the silicon-based particles in at least one form of metal atoms, metal silicates, metal silicides, and metal oxides. The metal atoms may include at least one selected from the group consisting of Mg, Li, Al, and Ca. This can improve the initial efficiency of the negative electrode active material.
[0036] In one embodiment of the present invention, the silicon-based particles have a carbon layer on at least a part of the surface. In this case, the carbon layer may be partially coated on at least a part of the surface, i.e., the particle surface, or may be coated on the entire particle surface. The carbon layer imparts electrical conductivity to the negative electrode active material, and the initial efficiency, life characteristics, and battery capacity characteristics of the secondary battery may be improved.
[0037] In one embodiment of the invention, the carbon layer comprises amorphous carbon.
[0038] The carbon layer may further include crystalline carbon.
[0039] The crystalline carbon can further improve the electrical conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.
[0040] The amorphous carbon can appropriately maintain the strength of the carbon layer and suppress the expansion of the silicon-based particles. The amorphous carbon may be a carbon-based material formed by using at least one carbide or hydrocarbon selected from the group consisting of tar, pitch, and other organic substances as a source of a chemical vapor deposition process.
[0041] The carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose, or ketohexose, and combinations thereof.
[0042] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may include methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, or hexane. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may include benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, or phenanthrene.
[0043] In one embodiment of the present invention, the carbon layer may be an amorphous carbon layer.
[0044] In one embodiment of the present invention, the carbon layer may be included in an amount of 0.1 to 50 parts by weight, 0.1 to 30 parts by weight, or 0.1 to 20 parts by weight, based on 100 parts by weight of the total amount of the negative electrode active material. More specifically, the carbon layer may be included in an amount of 0.5 to 15 parts by weight, 1 to 10 parts by weight, or 1 to 5 parts by weight. When the amount is within the above range, a decrease in the capacity and efficiency of the negative electrode active material can be prevented.
[0045] In one embodiment of the present invention, the thickness of the carbon layer may be 1 nm to 500 nm, specifically, 5 nm to 300 nm. When the thickness satisfies the above range, the conductivity of the negative electrode active material is improved, the volume change of the negative electrode active material is easily suppressed, and the side reaction between the electrolyte and the negative electrode active material is suppressed, thereby improving the initial efficiency and / or the life of the battery.
[0046] Specifically, the carbon layer can be formed by chemical vapor deposition (CVD) using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene.
[0047] In one embodiment of the present invention, the silicon-based particles are provided with an inorganic layer containing Ca on at least a part of the surface thereof. Specifically, during the preparation of the negative electrode active material, silicon-based particles having a carbon layer on at least a part of the surface thereof are formed, and then doped with Li, and then a Ca precursor is used to introduce an inorganic layer containing Ca on at least a part of the surface of the silicon-based particles.
[0048] The Ca-containing inorganic layer may include an inorganic material containing Ca. In addition, the inorganic layer may further include other substances that are present during the reaction of the Ca precursor with the silicon-based particles.
[0049] The inorganic layer containing Ca formed as above is not easily dissolved in water and has low reactivity with water. As a result, the inorganic layer is well retained in the aqueous slurry without reacting with water, preventing water from penetrating into the negative active material, and therefore the silicon-based particles can be efficiently passivated. In addition, the Li compound contained in the silicon-based particles is prevented from being eluted, and the slurry is prevented from becoming basic, improving the aqueous processability. Furthermore, the Ca precursor for forming the inorganic layer containing Ca is easy to synthesize as a salt and is relatively easy to obtain, which is more advantageous in achieving the above-mentioned effects.
[0050] In one embodiment of the present invention, the Ca-containing inorganic layer may be provided on at least a portion of the carbon layer, or may be provided on at least a portion of an area of the silicon-based particle surface where no carbon layer is provided.
[0051] The inorganic layer containing Ca may be in a form in which the surface of the silicon-based particle or the carbon layer is partially covered, or the entire surface is covered. The shape of the inorganic layer containing Ca may be an island type or a thin film type, and specifically, the inorganic layer may be in an island type.
[0052] The Ca-containing inorganic layer may include at least one selected from the group consisting of CaCO3, CaO, and Ca(OH)2. Specifically, the Ca-containing inorganic layer may include CaCO3 or Ca(OH)2. The components of the Ca-containing inorganic layer are not limited thereto, and may include, for example, a Ca-containing inorganic material that can be formed using a Ca precursor known in the art.
[0053] The components contained in the negative electrode active material can be identified by X-ray diffraction analysis (XRD) or SEM-EDX.
[0054] In one embodiment of the present invention, the negative active material may have a peak at 29° to 30° in XRD analysis. The peak at 29° to 30° may be a peak due to Ca and may be in the form of a shoulder peak.
[0055] In one embodiment of the present invention, an additional peak may be present at 28° to 29° in X-ray diffraction (XRD) analysis of the negative active material. The peak at 28° to 29° may be a peak due to Si, and the peak due to Ca may be present in the form of a shoulder peak to the right of the peak due to Si.
[0056] As an example, FIG. 1 is an XRD analysis graph of the negative active material prepared in Example 1 described below. It can be seen that a peak due to Si appears at 28° to 29°, and a peak due to Ca is detected in the form of a shoulder peak at 29° to 30°.
[0057] In the present invention, the Ca content on the surface of the negative active material can be analyzed by scanning electron microscope-energy dispersive X-ray analysis (SEM-EDX), specifically, using a Hitachi S-4800 at an accelerating voltage of 15 kV and a working distance of 15 mm.
[0058] In one embodiment of the present invention, when the negative electrode active material is analyzed by scanning electron microscope-energy dispersive X-ray analysis (SEM-EDX), the Ca may be contained in an amount of 0.05 to 10 parts by weight. Specifically, the Ca may be contained in an amount of 0.1 to 5 parts by weight or 0.5 to 4 parts by weight. The upper limit of the Ca content may be 10 parts by weight, 8 parts by weight, 5 parts by weight, or 4 parts by weight, and the lower limit may be 0.05 parts by weight, 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, 0.7 parts by weight, or 0.8 parts by weight. The Ca content may be based on an area analyzed by SEM-EDX on the surface of the negative electrode active material at an accelerating voltage of 15 kV and a working distance of 15 mm.
[0059] In one embodiment of the present invention, the Ca may be included in an amount of 0.005 to 5 parts by weight based on 100 parts by weight of the total negative electrode active material. Specifically, the Ca may be included in an amount of 0.01 to 3 parts by weight or 0.1 to 2 parts by weight. The upper limit of the Ca content may be 5 parts by weight, 4 parts by weight, 3 parts by weight, or 2 parts by weight, and the lower limit may be 0.005 parts by weight, 0.01 parts by weight, 0.1 parts by weight, 0.2 parts by weight, or 0.3 parts by weight.
[0060] In one embodiment of the present invention, the inorganic layer containing Ca may be included in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of the total negative electrode active material. Specifically, the inorganic layer containing Ca may be included in an amount of 0.1 to 5 parts by weight, 0.4 to 5 parts by weight, or 0.5 to 4 parts by weight. The upper limit of the content of the inorganic layer containing Ca may be 10 parts by weight, 8 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, or 3.5 parts by weight, and the lower limit may be 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, or 0.7 parts by weight.
[0061] When the content range is satisfied, the negative active material is prevented from reacting with water in the aqueous slurry or from dissolving lithium by-products, thereby improving aqueous processability. On the other hand, when the content exceeds the range, the inorganic layer containing Ca does not participate in the electrochemical reaction, resulting in a problem of reduced capacity and efficiency of the negative active material. When the content is less than the range, the inorganic layer containing Ca cannot adequately perform the role of passivation.
[0062] In one embodiment of the present invention, the silicon-based particle may further include a lithium by-product provided on at least a part of the silicon-based particle. Specifically, the lithium by-product may be present on the surface of the silicon-based particle or on the surface of the carbon layer. The lithium by-product may also be present between the Ca-containing inorganic layer and the silicon-based particle.
[0063] Specifically, the lithium by-product may refer to a lithium compound remaining near the surface of the silicon-based particles or the carbon layer after the silicon-based particles are manufactured. As described above, even after the acid treatment process, lithium by-products that have not reacted with the acid may remain.
[0064] The lithium by-products may include one or more selected from the group consisting of Li2O, LiOH, and Li2CO3.
[0065] The presence or absence of the lithium by-product can be confirmed by X-ray diffraction analysis (XRD) or X-ray photoelectron spectroscopy (XPS).
[0066] The lithium by-product may be contained in an amount of 5 parts by weight or less based on 100 parts by weight of the entire negative electrode active material. Specifically, it may be contained in an amount of 0.001 to 5 parts by weight, 0.01 to 5 parts by weight, 0.05 to 2 parts by weight, or 0.1 to 1 part by weight. More specifically, it may be contained in an amount of 0.1 to 0.8 parts by weight or 0.1 to 0.5 parts by weight. When the content of the lithium by-product satisfies the above range, side reactions in the slurry can be reduced, changes in viscosity can be decreased, and aqueous system processability characteristics can be improved. On the other hand, when the content of the lithium by-product is higher than the above range, there are problems such as the slurry becoming basic during formation, which causes side reactions and changes in viscosity, resulting in problems with aqueous system processability.
[0067] The content of the lithium by-product can be calculated by measuring the amount of the HCl solution in a specific section where the pH changes during the process of titrating an aqueous solution containing the negative electrode active material with an HCl solution using a titration device.
[0068] The average particle size (D 50 ) of the negative electrode active material may be 0.1 μm to 30 μm, specifically, it may be 1 μm to 20 μm, and more specifically, it may be 1 μm to 10 μm. When the above range is satisfied, the structural stability of the active material during charge and discharge can be achieved, preventing problems such as the particle size becoming excessively large and the volume expansion / contraction level also increasing, and preventing problems such as the particle size becoming excessively small and the initial efficiency decreasing.
[0069] <Method for manufacturing negative electrode active material> One embodiment of the present invention includes the steps of forming silicon-based particles containing SiO x (0 < x < 2) and an Li compound and having a carbon layer provided on at least a part of the surface; and reacting the silicon-based particles with a Ca precursor; to provide a method for manufacturing the negative electrode active material.
[0070] The silicon-based particles may be formed by the steps of: vaporizing Si powder and SiO2 powder by heating in a vacuum, and then depositing the vaporized mixed gas to form preliminary particles; forming a carbon layer on the surface of the formed preliminary particles; and mixing the preliminary particles with the carbon layer formed thereon and Li powder, followed by heat treatment.
[0071] Specifically, the mixed powder of the Si powder and the SiO2 powder can be heat treated at 1300°C to 1800°C, 1400°C to 1800°C, or 1400°C to 1600°C under vacuum.
[0072] The formed preliminary particles may have the morphology of SiO.
[0073] The carbon layer can be formed by chemical vapor deposition (CVD) using a hydrocarbon gas or by carbonizing a material serving as a carbon source.
[0074] Specifically, the preliminary particles are fed into a reactor, and then a hydrocarbon gas is subjected to chemical vapor deposition (CVD) at 600° C. to 1200° C. The hydrocarbon gas may be at least one type of hydrocarbon gas selected from the group including methane, ethane, propane, and acetylene, and the gas may be heat-treated at 900° C. to 1000° C.
[0075] The step of heat treating the preliminary particles on which the carbon layer is formed and the Li powder after mixing them may be performed at 700° C. to 900° C. for 4 to 6 hours, specifically, at 800° C. for 5 hours.
[0076] The silicon-based particles may include the Li compound such as Li silicate, Li silicide, or Li oxide.
[0077] The particle size of the silicon-based particles can be adjusted by a method such as, but not limited to, a ball mill, a jet mill, or air flow classification.
[0078] As described above, at least a part of the surface of the silicon-based particles provided with the carbon layer is provided with a lithium compound (lithium by-product). Specifically, the SiO x (0 < x < 2) to form preliminary particles, and after forming a carbon layer on the preliminary particles, Li is doped to produce the silicon-based particles. In this process, a lithium compound, that is, a lithium by-product formed by unreacted lithium, remains near the surface of the silicon-based particles.
[0079] In one embodiment of the present invention, the method for manufacturing the negative electrode active material includes a step of reacting the silicon-based particles with a Ca precursor.
[0080] Specifically, the step of reacting the silicon-based particles with the Ca precursor can be performed by mixing the silicon-based particles and the Ca precursor and then heat-treating the mixture.
[0081] The mixture of the silicon-based particles and the Ca precursor may be heat-treated at a temperature of 500°C to 1200°C in an argon atmosphere. Specifically, it may be heat-treated at 550°C to 1000°C or 600°C to 800°C for 1 hour to 5 hours or 2 hours to 4 hours. By this heat treatment process, an inorganic layer containing Ca is formed on the surface of the silicon-based particles.
[0082] The Ca precursor may be, for example, Ca(OAc)2, CaCl2, CaO, or Ca(NO3)2, and is not limited thereto. Appropriate Ca precursors known in the art may be adopted and used.
[0083] The content of the Ca precursor may be 0.01 to 20 parts by weight, specifically 0.1 to 15 parts by weight or 1 to 12 parts by weight, based on 100 parts by weight of the total mixture of the silicon-based particles and the Ca precursor. The lower limit of the content of the Ca precursor may be 0.01 parts by weight, 0.1 parts by weight, 1 parts by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight or 8 parts by weight, and the upper limit may be 20 parts by weight, 18 parts by weight, 16 parts by weight, 14 parts by weight, 12 parts by weight or 10 parts by weight.
[0084] Specifically, an inorganic layer containing Ca is formed on the silicon-based particles from a Ca precursor, and the formed inorganic layer easily blocks the reaction between water and the lithium compound or the silicon-based particles, thereby suppressing gas generation from the slurry and improving the aqueous processability.
[0085] Furthermore, when a Ca precursor is used, the synthesis method of the inorganic layer containing Ca is simple, which is advantageous in terms of the manufacturing process of the negative electrode active material.
[0086] <Negative electrode> A negative electrode according to an embodiment of the present invention may include the negative electrode active material described above.
[0087] Specifically, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. Furthermore, the negative electrode active material layer may further include a binder, a thickener, and / or a conductive material.
[0088] The negative electrode active material layer may be formed by applying a negative electrode slurry including a negative electrode active material, a binder, a thickener, and / or a conductive material to at least one surface of a current collector, followed by drying and rolling.
[0089] The negative electrode slurry may further include an additional negative electrode active material.
[0090] The additional negative electrode active material may be a compound capable of reversibly inserting and extracting lithium. Specific examples of the additional negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, lithium titanium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, the carbon material may be either low-crystalline carbon or high-crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0091] The additional anode active material may be a carbon-based anode active material.
[0092] The negative electrode slurry may include a solvent for forming a negative electrode slurry. Specifically, the solvent for forming a negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of components.
[0093] The negative electrode slurry containing the negative electrode active material according to one embodiment of the present invention may have a pH of 7 to 11 at 25° C. When the pH of the negative electrode slurry satisfies the above range, the rheological properties of the slurry are stabilized. On the other hand, when the pH of the negative electrode slurry is less than 7 or exceeds 11, there is a problem that decomposition of carboxymethyl cellulose (CMC) used as a thickener occurs, causing a decrease in the viscosity of the slurry, and a decrease in the degree of dispersion of the active material contained in the slurry.
[0094] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector. The thickness of the current collector may be 6 μm to 20 μm, but is not limited thereto.
[0095] The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0096] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbons; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0097] The conductive material may be contained in an amount of 0.01% by weight to 30% by weight, and preferably 0.1% by weight to 20% by weight, based on 100% by weight of the negative electrode active material layer.
[0098] The thickener may be carboxymethyl cellulose (CMC), but is not limited thereto, and any thickener used in the art may be appropriately adopted.
[0099] In one embodiment of the present invention, the weight ratio of the negative electrode active material and the additional negative electrode active material contained in the negative electrode slurry may be 1:99 to 30:70, specifically, 5:95 to 30:70 or 10:90 to 20:80.
[0100] In an embodiment of the present invention, the total amount of the negative electrode active material contained in the negative electrode slurry may be 60 parts by weight to 99 parts by weight, specifically, 70 parts by weight to 98 parts by weight, based on 100 parts by weight of a total solid content of the negative electrode slurry.
[0101] In one embodiment of the present invention, the binder may be included in an amount of 0.5 to 30 parts by weight, specifically 1 to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0102] In one embodiment of the present invention, the conductive material may be included in an amount of 0.5 to 25 parts by weight, specifically 1 to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0103] In one embodiment of the present invention, the thickener may be included in an amount of 0.5 parts by weight to 25 parts by weight, specifically, 0.5 parts by weight to 20 parts by weight, more specifically, 1 part by weight to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0104] The negative electrode slurry according to an embodiment of the present invention may further include a solvent for forming the negative electrode slurry. Specifically, the solvent for forming the negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of components.
[0105] In one embodiment of the present invention, the weight of the solid content of the negative electrode slurry may be 20 parts by weight to 75 parts by weight, specifically 30 parts by weight to 70 parts by weight, based on 100 parts by weight of the total negative electrode slurry.
[0106] <Secondary battery> A secondary battery according to an embodiment of the present invention may include the anode according to the embodiment described above. Specifically, the secondary battery may include an anode, a cathode, a separator interposed between the cathode and the anode, and an electrolyte, and the anode is the same as the anode described above. The anode has been described above, so a detailed description thereof will be omitted.
[0107] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0108] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0109] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.
[0110] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0111] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and other carbon-containing substances; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one of these may be used alone or a mixture of two or more of them may be used.
[0112] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.
[0113] The separator is a separator that separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is normally used as a separator in a secondary battery can be used without any particular restrictions, and it is particularly preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte moisture absorption ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.
[0114] Examples of the electrolytic solution include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries.
[0115] Specifically, the electrolytic solution may contain a non-aqueous organic solvent and a metal salt.
[0116] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0117] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, can be preferably used as high-viscosity organic solvents, because they have a high dielectric constant and dissociate lithium salts well. When such cyclic carbonates are mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, an electrolyte solution having high conductivity can be prepared, and therefore such a mixture can be used even more preferably.
[0118] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.
[0119] In addition to the components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0120] According to another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. EXAMPLES
[0121] <Examples and Comparative Examples> Example 1 94g of powder of Si and SiO2 mixed in a 1:1 molar ratio was mixed in a reactor and then vacuum heated at a sublimation temperature of 1400°C. The vaporized Si and SiO2 mixed gas was then reacted in a vacuum cooling zone with a cooling temperature of 800°C to condense into a solid phase. The condensed particles were then pulverized in a ball mill for 3 hours to produce silicon-based particles with a size of 6μm. The silicon-based particles were then placed in the hot zone of a CVD device while Ar gas was flowed to maintain an inert atmosphere, and the methane was blown into the hot zone at 900°C using Ar as a carrier gas, and the mixture was heated for 10 minutes at 400°C. -1 The silicon-based particles were reacted at 1000 torr to form a carbon layer on the surface of the silicon-based particles. Then, 6 g of Li metal powder was added and subjected to additional heat treatment at 800°C in an inert atmosphere, and then Ca(OAc)2:silicon-based particles were mixed in a weight ratio of 2:98 and heated at 650°C for 3 hours in an argon atmosphere to produce an anode active material with a Ca-containing inorganic layer formed on the surface of the particles.
[0122] Example 2 A negative electrode active material was prepared in the same manner as in Example 1, except that the weight ratio of Ca(OAc)2:silicon-based particles was 10:90.
[0123] Example 3 After mixing the silicon-based particles and Ca(OAc)2, a negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment temperature was changed to 1000°C.
[0124] Comparative Example 1 A negative active material was prepared in the same manner as in Example 1, except that the process of mixing Ca(OAc)2 and heat treatment was not performed.
[0125] Comparative Example 2 A negative active material was prepared in the same manner as in Example 1, except that the process of adding the Li metal powder and performing the heat treatment was not performed.
[0126] <X-ray diffraction (XRD) analysis of negative electrode active material> Figure 1 is an XRD analysis graph of the negative active material prepared in Example 1, in which a peak due to Si appears at 28°~29°, and a shoulder peak due to Ca is detected at 29°~30°. Meanwhile, Figure 2 is an XRD analysis graph of the negative active material prepared in Comparative Example 1, in which a peak due to Si appears at 28°~29°, and no shoulder peak due to Ca is detected.
[0127] <Carbon layer content analysis> The content of the carbon layer was analyzed using a CS-analyzer (CS-800, Eltra).
[0128] <Analysis of Li content in negative electrode active material> The Li atom content was confirmed by ICP analysis using an inductively coupled plasma optical emission spectrometer (Perkin-Elmer 7300 ICP-OES, AVIO 500).
[0129] <SEM-EDX analysis of the surface of the negative electrode active material> The surface of the negative active material was analyzed by scanning electron microscope-energy dispersive X-ray analysis (SEM-EDX) using a Hitachi S-4800 at an accelerating voltage of 15 kV and a working distance of 15 mm.
[0130] <Analysis of Ca content and inorganic layer content in negative electrode active material> The Ca content was confirmed by ICP analysis using an inductively coupled plasma optical emission spectrometer (Perkin-Elmer 7300 ICP-OES, AVIO 500), and the Ca content in the negative active material and the content of the inorganic layer were analyzed.
[0131] <D of negative electrode active material 50 and non-surface area analysis> D of the negative electrode active material 50The particle size distribution was analyzed by laser diffraction particle size analysis using a Microtrac S3500 device, and the BET specific surface area of the negative active material was measured using a BET measuring device (BEL-SORP-MAX, Nippon Bell).
[0132] The analysis results of the negative active materials prepared in the above examples and comparative examples are shown in Table 1 below.
[0133] [Table 1]
[0134] <Experimental example: Discharge capacity, initial efficiency, life (capacity retention) characteristic evaluation> Negative electrodes and batteries were manufactured using the negative electrode active materials of the examples and comparative examples, respectively.
[0135] The negative electrode active material, carbon black as a conductive material, and PAA (polyacrylic acid) as a binder were mixed in a weight ratio of 80:10:10 to prepare a mixture. Then, 7.8g of distilled water was added to 5g of the mixture and stirred to prepare a negative electrode slurry. The negative electrode slurry was applied to a copper (Cu) metal thin film as a negative electrode current collector with a thickness of 20μm and dried. At this time, the temperature of the circulating air was 60°C. Then, the mixture was roll pressed and dried in a vacuum oven at 130°C for 12 hours to prepare a negative electrode.
[0136] The manufactured negative electrode is placed in a 1.7671 cm 2 A lithium (Li) metal thin film cut into a circular shape was used as the positive electrode. A porous polyethylene separator was placed between the positive electrode and the negative electrode, and an electrolyte solution in which 0.5 parts by weight of vinylene carbonate was dissolved in a mixed solution of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) with a volume ratio of 7:3, and LiPF6 with a concentration of 1M was dissolved was injected to prepare a lithium coin half-cell.
[0137] The produced battery was charged and discharged to evaluate the discharge capacity, initial efficiency, and capacity retention rate, and the results are shown in Table 2 below.
[0138] The first and second cycles were charged and discharged at 0.1 C, and the third to 49th cycles were charged and discharged at 0.5 C. The 50th cycle was completed in a charged state (with lithium in the negative electrode).
[0139] Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cut-off) Discharge condition: CC (constant current) condition 1.5V
[0140] The discharge capacity (mAh / g) and initial efficiency (%) were derived from the results of one charge / discharge. Specifically, the initial efficiency (%) was derived by the following calculation.
[0141] Initial efficiency (%) = (single discharge capacity / single charge capacity) x 100
[0142] The capacity retention rate was calculated as follows.
[0143] Capacity retention rate (%) = (49 times discharge capacity / 1 time discharge capacity) × 100
[0144] <Experimental example: Processability (gas generation) characteristic evaluation> As part of the processability evaluation, 20 g of a slurry prepared by mixing graphite: the negative electrode active material: carbon black: CMC: PAA in a weight ratio of 77:20:1:1:1 was placed in a pouch of about 10 cm x 15 cm, vacuum sealed, and then placed in an oven at 40°C to measure the volume change.
[0145] The time (hour) at which gas was generated was measured based on the time when the volume of the pouch increased by 2 mL or more relative to the volume measured immediately after the pouch was vacuum sealed, and is shown in Table 2 below.
[0146] [Table 2]
[0147] The negative electrode active material according to the present invention is characterized in that a Ca-containing inorganic layer is provided on silicon-based particles containing a Li compound, and since the inorganic layer has low reactivity with water, the inorganic layer does not react with water in the aqueous slurry and is well retained, preventing water from penetrating into the negative electrode active material. This makes it possible to efficiently passivate the silicon-based particles. In addition, the side reaction between the silicon-based particles or lithium by-products and water is prevented, and gas generation is suppressed, thereby improving the aqueous processability of the slurry.
[0148] In Table 2, it was confirmed that in Examples 1 to 3, the silicon-based particles were efficiently passivated by forming a Ca-containing inorganic layer on the silicon-based particles using a Ca precursor, and thus the overall discharge capacity, initial efficiency, and capacity retention were excellent compared to Comparative Example 1. In addition, side reactions in the aqueous slurry were prevented, and the time point of gas generation was delayed, ensuring excellent aqueous processability.
[0149] In the case of Comparative Example 2, the silicon-based particles were not doped with Li, so the discharge capacity was high, no lithium by-products were produced, and no gas was generated. However, it was confirmed that when the particles were not doped with Li, the initial efficiency and capacity retention rate were significantly reduced compared to Examples 1 to 3.
[0150] Therefore, in the present invention, by providing an anode active material having a Ca-containing inorganic layer on silicon-based particles containing a Li compound, it is possible to easily improve the overall aqueous processability, discharge capacity, efficiency, and capacity retention rate by utilizing the passivation effect.
Claims
1. SiO x (0<x<2) and a Li compound, and a silicon-based particle having a carbon layer on at least a portion of the surface thereof; and a Ca-containing inorganic layer provided on at least a portion of the silicon-based particle; A negative electrode active material comprising:
2. 2. The negative electrode active material according to claim 1, which has a peak at 29° to 30° in X-ray diffraction analysis.
3. The negative electrode active material according to claim 1 , wherein the Ca-containing inorganic layer is provided in an island shape on at least a part of the silicon-based particle.
4. The Ca-containing inorganic layer is CaCO 3 , CaO, and Ca(OH) 2 The negative electrode active material according to claim 1 , comprising at least one selected from the group consisting of:
5. 3. The negative electrode active material of claim 2, wherein the X-ray diffraction analysis shows an additional peak at 28° or more and less than 29°.
6. 2. The negative electrode active material according to claim 1, wherein the Ca element content is 0.05 to 10 parts by weight when analyzed by scanning electron microscope-energy dispersive X-ray analysis (SEM-EDX).
7. The negative electrode active material of claim 1, wherein the Ca is contained in an amount of 0.005 to 5 parts by weight based on 100 parts by weight of the total negative electrode active material.
8. The negative electrode active material of claim 1, wherein the Ca-containing inorganic layer is included in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of the total negative electrode active material.
9. The negative electrode active material of claim 1 , further comprising a lithium by-product provided on at least a portion of the silicon-based particles.
10. The negative electrode active material of claim 9 , wherein the lithium by-product is present in an amount of 5 parts by weight or less based on 100 parts by weight of the total negative electrode active material.
11. The negative electrode active material of claim 1, comprising 0.1 to 40 parts by weight of Li based on 100 parts by weight of the total negative electrode active material.
12. The negative electrode active material of claim 1, wherein the carbon layer is present in an amount of 0.1 to 50 parts by weight based on 100 parts by weight of the total negative electrode active material.
13. SiO x forming silicon-based particles comprising a (0<x<2) and Li compound, the particles having a carbon layer on at least a portion of the surface thereof; and reacting the silicon-based particles with a Ca precursor; The method for producing the negative electrode active material according to claim 1 , comprising:
14. A negative electrode comprising the negative electrode active material according to claim 1 .
15. A secondary battery comprising the negative electrode according to claim 14.
Citation Information
Patent Citations
Silicon composite negative electrode material, its preparation method and lithium ion battery
JP2022518585A
Negative electrode active material for rechargable lithium battery, method for manufacturing the same, and rechargable lithium battery including the same
KR1020170074030A